Wound healing activity of neferine in experimental diabetic rats through the inhibition of inflammatory cytokines and nrf-2 pathway. Issue 1 (1st January 2020) - Li, Juan; Chou, Haiyan; Li, Lei; Li, Hao; Cui, Zhengjun
Abstract: The diabetic foot ulcer (DFU) may be associated with late healing and septic manifestation, subsequently lead to amputation which is an overpriced incident. Neferine is an alkaloid found lotus. Neferine possesses many physiological functions such as anti-inflammatory, antioxidant, antimicrobial activity and anticancer effect. The aim of the present study was to evaluate the effect of topical application based on neferine, in streptozotocin-induced diabetic incision wound models rats. The data demonstrated wound healing activities via macroscopic, biochemical, histological, immuno-histochemical, immunofluorescent and molecular methods. There was significant acceleration in wound closure rate, decrease in the period of re-epitalization, higher amount of collagen and protein content in neferine treated group when compared with diabetic wound control. Histological data evidence collagen formation in skin and marked granulation with more connective tissue markers. The augmentation of serum insulin and HDL was dissimilar with blood glucose reduction and decreased lipid level (TC, TG and LDL). The healing effect was additionally validated by decreased lipid peroxidation and enhanced antioxidants. Concurrently, the mRNA level of Nrf-2, collagen-1, TGF-β and α-SMA were decreased with Kaep-1 increased significantly. This enhancement was achieved through downregulation of inflammatory mediators such as nuclear factor kappa-light-chain-enhancer of activated B cells, tumour necrosis factor-α, interleukin-1β, interleukin-8, inducible nitric oxide synthase, and cyclooxygenase-2, and upregulation of growth factor such as in groups treated with neferine. The western blot results reveal the macrophage (CD 68 and CD 163) involved in wound healing markedly elevated. Hence, the results indicate that neferine significantly promotes a fast and efficient wound healing in diabetic rats.